Konsumsi Kopi Robusta Menurunkan Kekuatan Tulang Femur Tikus Wistar Jantan - Sarah Kinan Andalusia; Muhamad Hasan; Desie Dwi Wisudanti (Pustaka Kesehatan, 2018)
Caffeine in coffee is suspected to decrease the bone mineral density and increase the risk factor of osteoporosis, however the contents of coffee is not only caffeine. Considering the great number of people consuming coffee daily, therefore, the study is conducted to investigate the effect of robusta coffee consumption on the femoral bone strength in male wistar rats. Thirty male wistar rats were subjected for the study. They were divided into three groups, i.e control group (K) without robusta coffee consumption, treatment group 1 (P1) with robusta coffee consumption of 0,9 mg/gBW, and treatment group 2 (P2) with robusta coffee consumption of 2,7 mg/gBW. After 21 days, the rats were terminated and the right and the left femurs were collected for force bone test. The force bone test of P1 and P2 group demonstrated weaker bones than K group, and there was no difference effect of P1 group compared to P2 group on the femoral bone strength in male wistar rats. It can be concluded that robusta coffee consumption has negative effect on the bone strenght and hence causing bones more fragile, and there was no difference on effect of 0,9 mg/g BW compared to 2,7 mg/g BW.